Patient safety climate and the intervention of the quality control circles: An empirical study at a general hospital in Taiwan - Weng, Shao-Jen; Kim, Seung-Hwan; Wu, Chieh-Liang; Liu, Shih-Chia; Jiang, Ying-Ye; Yang, Kuei-Fen; Gotcher, Donald; Tsai, Yao-Te (Asian Journal of Empirical Research, 2025)
Quality Control Circles (QCCs) were instituted. Through the use of the Safety Attitudes Questionnaire (SAQ), we aimed to demonstrate a correlation between QCCs and improvements in units’ Patient Safety Culture (PSC). This study utilized data collected by SAQs at Taichung Veterans General Hospital (TCVGH) in Taiwan. We investigated the relationships among the levels of units’ QCC participation and the dimensions of SAQs through methods such as latent class analysis (LCA) and generalized estimating equations (GEE). Approximately 30 QCC teams from 78 units (wards or divisions) participate annually. The participation of teams in QCCs is classified into “low,” “medium,” and “high” levels by LCA. Results indicate that higher QCC participation correlates with a greater reduction in performance on the dimension of “Job Satisfaction”; specifically, the performance scores for medium and high participation are 2.34 points and 2.83 points lower than those for low participation. Despite the reduction in “Job Satisfaction,” members in the high participation group continue to prioritize patient safety and demonstrate stronger stress resistance. Regarding quality improvement promoted through QCCs, units with higher participation should emphasize patient safety more. However, authorities need to pay increased attention to opinion acceptance and adoption, as well as employee well-being during the operation process.